Genetic diversity patterns of arbuscular mycorrhizal fungi associated with the mycoheterotroph Arachnitis uniflora Phil. (Corsiaceae) - Renny, Mauricio Eduardo (2017)
Background and Aims: Arachnitis uniflora is a mycoheterotrophic plant that exploits arbuscular mycorrhizal fungi of neighbouring plants. We tested A. uniflora's specificity towards fungi across its large latitudinal range, as well as the role of historical events and current environmental, geographical and altitudinal variables on fungal genetic diversity. Methods: Arachnitis uniflora mycorrhizas were sampled at 25 sites. Fungal phylogenetic relationships were reconstructed, genetic diversity was calculated and the main divergent lineages were dated. Phylogeographical analysis was performed with the main fungal clade. Fungal diversity correlations with environmental factors were investigated. Key Results: Glomeraceae fungi dominated, with a main clade that likely originated in the Upper Cretaceous and diversified in the Miocene. Two other arbuscular mycorrhizal fungal families not previously known to be targeted by A. uniflora were detected rarely and appear to be facultative associations. High genetic diversity, found in Bolivia and both northern and southern Patagonia, was correlated with temperature, rainfall and soil features. Conclusions: Fungal genetic diversity and its distribution can be explained by the ancient evolutionary history of the target fungi and by micro-scale environmental conditions with a geographical mosaic pattern.